Expectant mothers' not fathers' mind‐mindedness predicts infant, mother, and father conversational turns at 7 months. (26th August 2022) - Foley, Sarah; Hughes, Claire; Fink, Elian
Abstract: Parental mind‐mindedness (MM), defined as the propensity to view one's child as an agent with thoughts, feelings, and desires, is associated with positive child outcomes (McMahon & Bernier, 2017) and can be assessed in expectant parents by using five‐minute speech samples (Magaña et al., 1986). Individual differences in MM appear stable across the transition to parenthood (Foley et al., in press), offering an exciting intervention opportunity, as expectant mothers' thoughts and feelings about their unborn infants are associated with the quality of mother‐infant interactions. To assess prenatal MM as a predictor of parent‐infant conversation at 7 months, we followed 93 low‐risk British heterosexual couples across the transition to parenthood. Mothers' and fathers' MM was measured both in the third trimester of pregnancy and at 4 months. Wearable LENA devices were used to gather detailed measures of mother‐, father‐, and infant‐initiated conversations at 7 months. Prenatal MM in both parents was associated with more frequent infant‐initiated conversations at 7 months, while prenatal maternal (not paternal) MM was also associated with more mother‐ and father‐initiated conversations. While longitudinal research with more diverse samples is needed, these findings highlight the importance of parental mentalizing in the prenatal period for early family interactions.